2017
DOI: 10.4236/gep.2017.53007
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Basin Groundwater Transfer and Multiple Approach Recharge Estimation of the Upper Awash Aquifer System

Abstract: Multiple approaches have been used to estimate groundwater recharge in the Upper Awash river basin. The amount of recharge reaching the Upper Awash aquifer system from the Blue Nile sub-basins is also estimated. Water Balance, Chloride Mass Balance and HYDRUS 1D infiltration model are used to estimate recharge. A total of 29 sites were selected for the HYDRUS 1D multiple "at point" recharge simulations. Base Flow Separation (BFS) methods, using both River Analysis Package software Version 3.0.3 and Excel-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The Muger sub-basin is located to the southeast of the Abay Basin. Studies ( Azagegn et al, 2015 ; Berehanu et al, 2017 ) show that the aquifer system is connected to the upper Awash basin, which drains towards the southeast. This singularity combined with a lack of data makes calibration of the Muger basin very difficult.…”
Section: Study Areamentioning
confidence: 99%
“…The Muger sub-basin is located to the southeast of the Abay Basin. Studies ( Azagegn et al, 2015 ; Berehanu et al, 2017 ) show that the aquifer system is connected to the upper Awash basin, which drains towards the southeast. This singularity combined with a lack of data makes calibration of the Muger basin very difficult.…”
Section: Study Areamentioning
confidence: 99%
“…Annual precipitation of only 1200 mm is distributed over two rainy seasons, so we used the cropping calendar from the eastern part of the Blue Nile basin. Recent studies showed that the aquifer system of the Muger sub-basin has a hydraulic connection with the aquifer system of the Upper Awash basin, a basin which does not drain into the Blue Nile [37,38].…”
Section: • Upper Abay Sub-basinmentioning
confidence: 99%
“…In the Muger sub-basin, this results from a very low measured base flow during the dry season, which could not be simulated properly. An explanation for this discrepancy is the aquifer system of the Muger sub-basin, which has a connection with the aquifer system of the Upper Awash basin [37,38]. These water losses were not included in the model setup.…”
Section: Calibration-uncertainty Analysismentioning
confidence: 99%
“…Following recommended approaches, for example, Scanlon et al (2002) and Healy (2010), several techniques were initially applied, and it was found that they gave a wide range of recharge estimates. This is commonly reported in the literature, for example, Berehanu et al (2017); Afrifa et al (2017), although it is less common for studies to report investigation of the reasons for the range of values. Some previous studies, typically using at most three to five recharge estimation techniques, have considered the basis for differing recharge estimates in more detail, and concluded that the range of recharge estimates contains useful information to inform further understanding of the conceptual model (e.g., Coes et al 2007;King et al 2017).…”
Section: Introductionmentioning
confidence: 98%